Penerapan Algoritma SHA-384 Pada Aplikasi Duplicate Video Scanner - Hanafiah, Muhammad (Bulletin of Data Science, 2023)
Cryptography is used to maintain the security of private information from anyone except those with the authority or secret keys to access encrypted information. However, with the rapid advancement of computer technology, challenges to information security are increasing. Video manipulation is one of the serious threats in the digital world today. Video manipulation is a common phenomenon where individuals can easily manipulate videos with harmful intent or to confuse others. One of the most dangerous types of video manipulation is the duplicate video scanner, in which a fake video is created to resemble the original video in many aspects, including color, shape, objects, and content, without significant changes from other parties. This can deceive many viewers and cause significant losses. In this research, the author proposes the use of the SHA-384 algorithm as a method to detect duplicate video scanners. This algorithm is used to generate a unique signature or hash from video data, which is then used to verify the authenticity of the video. The results of this research have great potential in addressing serious issues related to video manipulation. The ability to distinguish real videos from fake ones has a significant impact in various fields, including law, security, and information integrity. This research provides an effective solution to ensure video authenticity and can help combat the increasing fraud and manipulation in a complex digital environment.